Pisidia longimana (Risso, 1816), a junior synonym of P. bluteli (Risso, 1816) (Crustacea: Decapoda: Anomura: Porcellanidae) and a species distinct from P. longicornis (Linnaeus, 1767) - Ferreira, Luciane Augusto de Azevedo; Tavares, Marcos (Papéis Avulsos de Zoologia, 2020)
Pisidia longimana (Risso, 1816) and P. bluteli (Risso, 1816), both described from Nice, France, have been considered each other’s synonyms or have been validated depending on successive taxonomic opinions. The validity of both in respect to P. longicornis (Linnaeus, 1767) has also been contradicted a number of times. The current lack of clarity in the use of the names P. longicornis, P. longimana and P. bluteli has resulted in nomenclatural instability, but also in unreliability and miscommunication as regards the available ecological and distributional information. The validity of P. bluteli and P. longimana is revisited herein based on a large number of specimens (241 males, 190 females and 33 juveniles) from many different localities. The latter species is confirmed as a junior synonym of the former, whereas P. bluteli and P. longicornis are herein considered separate species. Diagnostic characters and morphological variations are discussed and illustrated.